THE IMPACT OF CORPORATE GOVERNANCE, PROFITABILITY AND LIQUIDITY TOWARD FINANCIAL DISTRESS IN CONSUMER GOODS INDUSTRY LISTED AT INDONESIA STOCK EXCHANGE - Thania Luis; Frinan Frinan (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The purpose of this research is to examine the impact of corporate governance, profitability and liquidity toward financial distress on consumer goods industry companies listed at Indonesia Stock Exchange (IDX) from 2018 to 2020. This study is using three independent variables namely corporate governance proxies by institutional ownership, profitability assessed by return on assets (ROA) and liquidity assessed by current ratio (CR). The original Altman Z-Score, designed for public manufacturing companies, is used to measure financial distress. This research is using secondary data that gathered from consumer goods industry listed at Indonesia Stock Exchange (IDX) from 2018 to 2020. Using purposive sampling method, 28 consumer goods industry companies are selected as sample. Since this research is conducted starting from 2018 to 2020, the total sample is 84 observations. Data analysis method utilized in this research is multiple linear regression that processed by Statistical Product and Service Solutions 25 (SPSS 25). The result of this study shows that corporate governance (institutional ownership) and liquidity (CR) do not give a significant impact on financial distress. While profitability (ROA) has a significant impact on financial distress. Simultaneously, those three independent variables have significant impact on financial distress.